Effects of self‐efficacy, self‐esteem, and disability acceptance on the social participation of people with physical disabilities: Focusing on COVID‐19 pandemic - Hyeong‐min Kim (Brain and Behavior, 2023)
Abstract Purpose The objective of this study was to understand the effects of self‐efficacy, self‐esteem, and the degree of disability acceptance of people with physical disabilities living in COVID‐19 pandemic on their social participation. Methods Among the 4577 registered disabled people who participated in the 2nd wave of the Panel Survey of Employment for the Disabled (PSED), 1682 people with physical disabilities who faithfully answered all the survey items were selected as the final study subjects. This study used the variables of social participation, self‐efficacy, self‐esteem, and disability acceptance, which were validated by experts’ review and consulting and research at the Korea Employment Agency for Persons with Disability. Pearson's correlation analysis and multiple linear regression analysis were performed to identify variables that could predict the social participation of the study subjects. Results The self‐efficacy, self‐esteem, and the degree of disability acceptance of people with physical disabilities were positively correlated with social participation. The results of this study showed that self‐efficacy, self‐esteem, the degree of disability acceptance, economic activity, and education level explained 22.4% of social participation. Conclusions It was found that self‐efficacy, self‐esteem, and the degree of disability acceptance of people with physical disabilities were important variables affecting social participation. These psychoemotional variables shall be considered for intervention approaches to improve the social participation of people with physical disabilities in the future.